Land-structure split tax system in Korea - Lee, Jaeho (KDI School, 2011)
The purpose of this paper is to see if the two-rate tax shrinks supply of building spatial area per land. For that I used panel data of fifteen different cities and provinces. The government of South Korea has changed its real estate tax system from two-rate tax to compounded tax for housing but not for commercial building. Therefore, in this paper, it is tested whether changed tax system encouraged or discouraged the supply of spatial area for housing. For the tax system of the commercial building is consistent with the same period, it is tested whether the tax ratio between land and improvement affects the supply of spatial area. The result, it is revealed that either lower building tax or higher building tax encourages capital intensity. Therefore, we can say that to improve capital intensity; in other words, to use land more efficiently, the government has to collect more tax on land and less on building. Policy implication is drawn.
Thesis(Master) --KDI School:Master of Public Policy,2011